A detailed investigation of the core@shell structure of exchanged coupled magnetic nanoparticles after performing solvent annealing. Issue 23 (20th October 2022) - Sartori, Kevin; Ihiawakrim, Dris; Lefèvre, Christophe; Reguer, Solenn; Mocuta, Cristian; Bégin-Colin, Sylvie; Choueikani, Fadi; Pichon, Benoit P.
Abstract : Solvent annealing at around 300 °C resulted in a significant modification of the structure and the magnetic properties of core–shell metal oxide nanoparticles as shown by DANES and XMCD. Abstract : Thanks to important advances in synthesis techniques, a wide collection of bimagnetic core–shell nanoparticles with tunable properties was reported in the literature. Such nanoparticles may combine two phases with different intrinsic magnetic properties (magnetization, anisotropy, coercive field, etc. ). Core–shell structures with large interfaces usually favor efficient exchange coupling between both phases that may result in the enhancement of the effective magnetic anisotropy energy and of the coercive field. In this context, the chemical composition and the crystal structure of the core/shell interface in nanoparticles are crucial parameters to modulate efficiently their magnetic properties. Here, we report on the solvent mediated thermal annealing of Fe3− δ O4 @CoO nanoparticles in a high boiling point solvent. The structure of nanoparticles was investigated before and after thermal annealing by advanced characterization techniques such as high resolution transmission electron microscopy (HR-TEM), X-ray absorption spectroscopy (XAS), X-ray magnetic circular dichroism (XMCD) and diffraction anomalous near edge structure (DANES). The combination of DANES and XAS/XMCD allowed studying the cationic distribution in spinel and wüstite crystal structures as a function of site occupancy and oxidation state. To the best of our knowledge, it is the first time that DANES is performed to quantitatively investigate the chemical composition of biphasic metal oxide nanoparticles. Hence, we have investigated precisely the chemical composition of the spinel phase and that of the wüstite phase. Besides the partial solubilisation of the CoO shell observed by HR-TEM, thermal annealing favors the formation of a thicker intermediate Co-doped ferrite layer at the spinel/wüstite interface. Such significant modifications of the core@shell structure markedly influence interfacial coupling phenomena between the core and the shell, hence offering wide perspectives towards nanoparticles with tunable magnetic properties for a variety of applications.